Struktur dan Kaidah Kebahasaan Kumpulan Cerita Fabel dalam Buku Teks Bahasa Indonesia Kelas VII - Helmi, Tia Delpira (J-LELC: Journal of Language Education, Linguistics, and Culture, 2022)
Fable stories are animal stories intended to personify human characters. The animals that are used as story characters can talk, behave, and behave like humans. This research is entitled "The Structure and Language Rules of a Collection of Fable Stories in Indonesian Language Textbooks for Class VII". The problems contained in this study are: (1) what is the structure of the collection of fable stories in Indonesian class VII textbooks? (2) what are the linguistic rules of a collection of fable stories in Indonesian class VII textbooks?. The purpose of this study is to find out how the structure and linguistic rules of a collection of fable stories in Indonesian textbooks for class VII are. This study uses a qualitative research approach and content analysis research methods (Content Analysis). The theories used in this research are: Nurgiyantoro (2013), Emzir and Rohman (2015), Alwi. H, et al (2003). The data of this research are the structure of fable stories and the linguistic rules of fable stories contained in 17 fable stories published by the 2016 revised edition of the Ministry of Education and Culture and Erlangga publisher. The results showed that the structure of the fable story in the orientation section contained 16 fable stories that included and fulfilled the concept of orientation structure and one fable that did not include and did not meet the orientation structure concept, because the one fable story did not explain the place where the story took place. In the complication and resolution section, 17 fable stories are included and fulfill the concept of complication and resolution structure. In the coda section, there are 16 fable stories that are included and fulfill the coda structure concept and one fable story that does not include and does not meet the coda structure concept, because the researcher did not find any use of coda structure in the story. Meanwhile, in the linguistic rules of fable stories, there are 228 verbs and their classifications, 44 uses of the article sang and si, 81 uses of place and time, and 48 uses of conjunctions then, then, and finally.